Pengaruh Kepuasan Kerja, Budaya Organisasi dan Keterlibatan Kerja pada Organizational Citizenship Behavior - Utami, Rizky Marisa; Palupiningdyah, Palupiningdyah (Universitas Negeri Semarang, 2016)
This study aims to determine the effect of job satisfaction, organizational culture, and job involvement on organizational citizenship behavior on the employees of PT Mazuvo Indo Semarang. The population in this study was all employees of PT Mazuvo Indo Semarang amounting to 51 respondents. The sampling technique in this study using the technique of non-probability sampling with this type of sampling saturated, namely the determination of the sample if all members of the population used as a sample. The analysis method used in the study are instruments test (validity and reliability test), the classical assumption test, multiple regression analysis and hypothesis testing through partial test and simultaneous test with SPSS for Windows vertion 21. Data were collected by using interviews, questionnaires and literature study. The results from this study showed that the partial job satisfaction positive influence on OCB. There is a positive influence organizational culture on OCB and there is a positive influence job involvement on OCB. The conclusions of this study are job satisfaction, organizational culture, and job involvement influence on OCB.